Kajian Erosi Tanah menggunakan Isotop 137Cs dan 210Pb Excess di Sub DAS Ciesek, DAS Ciliwung Hulu, Bogor - Kukuh Murtilaksono; Ania Citraresmini; Sri Malahayati Yusuf; Taufik Bachtiar; Dwi Mei Lawaswati (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Fallout radio nuclides method has been being applied and developed to study and measure soil erosion for long time. This research aims to predict soil erosion/deposition in Ciesek subwatershed, Upper Ciliwung watershed using natural fallout radionuclides of 137Cs and 210Pb excess. Soil samples were taken using soil core along four transects of different land use types. Soil samples were analyzed using Multi Channel Analyzer (MCA) to obtain inventory value of the radioisotopes. The research shows different distribution pattern of soil erosion/deposition of 137Cs and 210Pb excess isotopes. Application of 137Cs isotope shows soil erosion process under home mix garden and dryland farm, but soil deposition process occurs on bareland. In the contrary, 210Pb excess indicates soil erosion on bare land while soil deposition is under home mix garden and dryland farm. Application of 210Pb excess is more reliable than 137Cs in predicting soil erosion.